Power Deficit Analysis of Multiple Hydrokinetic Power Plants in an Open-Channel System - Ikhsan, Muhammad; Zufrizal, Zufrizal; Taufik, Taufik (PTE FTK UIN Ar-Raniry, 2024)
The electricity generation capacity of hydrokinetic power plants can be enhanced by paralleling multiple plants simultaneously. This study focuses on the longitudinal configuration of multiple hydrokinetic turbines installed in a water channel. The energy production rate of downstream turbines is lower than that of upstream turbines when placed close to each other. This observed phenomenon, related to the wake effect, has resulted in reduced flow velocity. In this research, a power deficit technique is employed as an alternative to the velocity deficit strategy. By estimating the open flow characteristic, or k*, this method aims to predict the downstream power input at any given time. Without directly measuring water velocity, power can be predicted using the power deficit model. A hybrid model combining the Bastankhah Porté-Agel model and the Geometry-Based model has been utilized in this study. The analysis results indicate that the power deficit and velocity deficit values differ by an average of 1.3% and 0.15%, respectively.